Irrational Exuberance in the U.S. Housing Market : Were Evangelicals Left Behind? - Crowe, Christopher (IMF Working Papers; Working Paper ;, 2009)
The recent housing bust has reignited interest in psychological theories of speculative excess (Shiller, 2007). I investigate this issue by identifying a segment of the U.S. population-evangelical protestants-that may be less prone to speculative motives, and uncover a significant negative relationship between their population share and house price volatility. Evangelicals' focus on Biblical prophecy could account for this difference, since it may enable them to interpret otherwise negative events as containing positive news, dampening the response of house prices to shocks. I provide evidence for this channel using a popular internet measure of "prophetic activity" and a 9/11 event study. I also analyze survey data covering religious beliefs and asset holding, and find that 'end times' beliefs are associated with a one-third decline in net worth, consistent with these beliefs providing a form of psychic insurance (Scheve and Stasavage, 2006a and 2006b) that reduces asset demand.